The Effectiveness of Engklek through Flascard in Teaching Vocabulary - Anggraini, Nina; Candraloka, Olyvia Revalita (Universitas Nurul Jadid, 2025)
This study aimed to examine the effectiveness of using flashcards integrated with the traditional game engklek to improve English vocabulary mastery among seventh-grade students at MTs Al-Falah, Tuban. A quantitative approach with a quasi-experimental design (Nonequivalent Control Group Design) was employed. The sample included two classes: the experimental group (VII A), which received instruction using flashcards and the engklek game, and the control group (VII D), which received conventional instruction. Pretests and posttests were used as the primary instruments. The results revealed a significant improvement in the posttest scores of students in the experimental group compared to the control group. The paired samples t-test showed a significant value (p < 0.001) and a large effect size (Cohen’s d = 1.85). These findings indicate that a learning method combining traditional games and visual media is effective in enhancing vocabulary mastery, while also increasing student motivation and engagement. This approach is also suitable for schools with limited digital resources, particularly in rural areas.